2014
DOI: 10.1007/s10103-014-1640-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different surface treatments on the microtensile bond strength of two self-adhesive flowable composites

Abstract: The aim of this study was to evaluate the effect of different surface treatments on the microtensile bond strength (μTBS) of two different self-adhesive flowable composite materials (SACs) to dentin. Forty extracted human molars were horizontally flattened to expose the dentin surfaces. The teeth were divided into eight groups according to the surface treatments (acid etching, Er:YAG laser quantum square pulse (QSP) mode, and Er:YAG laser medium-short pulse (MSP) mode at 10 Hz, 1.2 W, 120 mJ, and control-SiC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 28 publications
8
25
0
4
Order By: Relevance
“…The laser-and acid-etched specimens served more regular surfaces than only laseretch groups and were similar with those of the acid-etch group. The SEM views of the present study are aligned with the study of Altunsoy et al 30) . When we evaluate the fractured surfaces after debonding in both laser irradiated groups, resin shows more integration to the dentin surface in total etch groups than self etch groups.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The laser-and acid-etched specimens served more regular surfaces than only laseretch groups and were similar with those of the acid-etch group. The SEM views of the present study are aligned with the study of Altunsoy et al 30) . When we evaluate the fractured surfaces after debonding in both laser irradiated groups, resin shows more integration to the dentin surface in total etch groups than self etch groups.…”
Section: Discussionsupporting
confidence: 76%
“…Altunsoy et al reported that the highest μTBS was recorded when Vertise Flow (self-adhesive flowable resin) was applied with acid etching, with no statistically significant differences between the QSP and MSP modes. However, in the same study, the highest μTBS for Fusio Liquid Dentin (self-adhesive flowable resin) was recorded with the MSP mode 30) . Filtek TM Ultimate Flowable Restorative was used in the current study.…”
Section: Discussionmentioning
confidence: 73%
“…This indicates a decline in the concentration of Ca. This phenomenon is similar to decalcification of the tooth [20]. Moreover, Brulat et al mentioned that dentin conditioning by low fluence with Er:YAG laser improved adhesion of composite resin to dentin [17, 21].…”
Section: Introductionmentioning
confidence: 92%
“…Affected area is less intense in the surrounded irradiated surface and deeper in the tissue layers [18]. This thermal damage increases gradually with the intensification of laser energy [20] and when temperature exceeds 225°C. Collagen fibers start to denature and no reversion to initial conformation is observed after rehydration [19].…”
Section: Introductionmentioning
confidence: 99%
“…Bond strength of composite resin is another concerning issue in released literature [40-44]. Some studies experienced “laser etching effect” by irradiating laser to prepare sufficient surface roughness and permitting mechanical interlocking with adhesive resins [22, 45].…”
Section: Materials and Methodologymentioning
confidence: 99%